Pentingnya Keterampilan Guru Untuk Menciptakan Pembelajaran Yang Menyenangkan - Yuli Mulya Mulyawati (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Teachers as educators need to master various skills to achieve learning objectives. This writing aims to determine the importance of teacher skills in creating fun learning. To achieve educational goals, one of the efforts that can be improved is the skills of teachers in implementing learning where students can play a role in active, creative, innovative and effective learning. This writing uses the Literature Review method. Where the source of this writing is obtained from various journals written by other authors as writing material. In this writing, there are various stages including 1) compiling the topic to be studied, 2) looking for reference sources or references as writing material, 3) the data obtained are used as a reference in writing for discussion and conclusions. Based on the results of research and discussion, it can be seen that the importance of skills to be mastered by teachers so that the learning carried out can provide a pleasant learning atmosphere. These skills include skills in using learning media, learning models, and teaching skills.